Reflector and Pragmatic Learning Styles in Learning Value Clarification Technique (VCT) and Direct Instruction (DI) - Sri Yunita; Abdul Hamid K; Hamonangan Tambunan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study used a quasi-experimental research type (quasi-experimental) with a 2 x 2 factorial design. The research sample was taken by cluster random sampling where one group was treated with the VCT learning model with a sample size of 50 people and one group was treated with the DI learning model with the number of a sample of 51 people. The data collection instruments used were Civics learning outcomes test and learning style questionnaire. The results of hypothesis testing conclude that: 1) There is an influence of the interaction between the learning model and student learning styles on learning outcomes, 2) the learning outcomes of students who have a reflector learning style learned with the VCT learning model are higher than those taught with the DI learning model.